2016
DOI: 10.1007/s00508-016-0986-9
|View full text |Cite
|
Sign up to set email alerts
|

Adipositas und Typ 2 Diabetes

Abstract: Zusammenfassung Adipositas und Typ 2 Diabetes werden heute gerne unter dem Namen „Diabesity“ zusammengefasst. Das trägt dem Umstand Rechnung, dass die Adipositas dem Diabetes häufig vorangeht und wohl der wichtigste Faktor in der Zunahme des Typ 2 Diabetes mellitus ist. Der Body-Mass-Index (BMI) ist nur ein sehr grobes Maß der Körperverfettung. Sogar Normalgewichtige können bei Muskelmangel zu viel Körperfett aufweisen (Sarkopenie), weswegen Messungen des Bauchumfanges und des Körperfettes empfohlen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…It has also been reported that hypoglycemic drugs such as metformin regulate the balance of intestinal microbiota and achieve the purpose of treating diabetes [29]. It was discovered that the abundance of Clostridium in the intestine of diabetic rats was signi cantly reduced [10]. At the same time, Denmark's study of 134 pre-diabetes patients reported that the abundance of Clostridium was signi cantly reduced [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that hypoglycemic drugs such as metformin regulate the balance of intestinal microbiota and achieve the purpose of treating diabetes [29]. It was discovered that the abundance of Clostridium in the intestine of diabetic rats was signi cantly reduced [10]. At the same time, Denmark's study of 134 pre-diabetes patients reported that the abundance of Clostridium was signi cantly reduced [27].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the bacterial species of interest in all subjects, qPCR was used to analyze the original DNA samples using bacterial species-speci c primers. The qPCR data were expressed as log 10 copies per mg total microbial DNA as showed in Figure 1. The abundance of Lactobacillus genus and Clostridium genus was lower in newly diagnosed T2DM group than in the NC group (P<0.05).…”
Section: Genotyping Of Ometin-1 Gene Variation (Rs2274907)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that hypoglycemic drugs such as metformin regulate the balance of intestinal microbiota and achieve the purpose of treating diabetes [29]. It was discovered that the abundance of Clostridium in the intestine of diabetic rats was significantly reduced [10]. At the same time,…”
mentioning
confidence: 98%
“…Gut microbiota closely related to the obesity [9], and obesity is important risk factor of T2DM [10].…”
mentioning
confidence: 99%